An In-depth Study of Relation Between Band Gap Energy and Lattice Constant for Cubic Phase LiSnX3 (X = F, Cl, Br, and I) Perosvkite - Ong, Russell; Sagala, Junaina Sahputri; Rahayu, Siti Utari (Journal of Technomaterial Physics, 2025)
Organic perovskites or inorganic perovskites are very popular among researchers who are designing the most efficient perovskite solar cells. Besides, they can be used as materials for other optoelectronic applications, such as light-emitting diodes. In this paper, we reported the results of studies on the electronic property of LiSnX3 (X = F, Cl, Br, or I) perovskite in the cubic phase. This electronic property is the density of states, which one can determine the band gap energy value. These studies were undertaken to understand the relation between their band gap energy and lattice constant through anion X variations. The Quantum ESPRESSO program calculated These two crucial quantities with norm-conserving Troullier-Martins pseudopotentials and Generalized Gradient Approximation Perdew-Burke-Enzerhof exchange-correlation functional. The computation results show that the band gap energy ranged from 0,3 eV to 0,99 eV while the lattice constant ranged from 6,183 Å to 4,625 Å for anion halide from I till F, respectively. The contrast trend between these quantities' values matches the Kronig-Penney Model.